Systematic Literature Review: Speech Intelligibility In Children With Repaired Cleft Lip Palate - Susanti, Nadya; Sudarman, Sudarman (Jurnal EduHealth, 2024)
Children with cleft lip and/or palate (CLP) frequently experience difficulties with speech and language development. Changes in the orofacial anatomical structure cause these issues, which lead to a restricted ability to articulate. Cleft lip and palate repair involves a variety of surgical techniques to restore function and a more normal appearance. This repair does not always result in normal function of the lip and palate, so these children usually present with speech difficulties even after surgery. Determining the speech intelligibility of CLP children who had undergone surgery was the goal of this investigation. The method used was to analyze the literature by searching for relevant articles on Pubmed, Wiley and Google Schoolar. Several reviews showed that speech intelligibility comprehension, measured using the Context Intelligibility Scale (CIS), depends on the proximity of the communication partner to the child. Although children with CLP have undergone surgery, speech therapy is still needed to help them improve speech intelligibility